Attitudes toward risk among emergency physicians and advanced practice clinicians in Massachusetts. Issue 5 (13th October 2021) - Smulowitz, Peter B.; Burke, Ryan C.; Ostrovsky, Daniel; Novack, Victor; Isbell, Linda; Landon, Bruce E.
Abstract : Objective: Risk aversion is a personality trait influential to decision making in medicine. Little is known about how emergency department (ED) clinicians differ in their attitudes toward risk taking. Methods: We conducted a cross‐sectional survey of practicing ED clinicians (physicians and advanced practice clinicians [APCs]) in Massachusetts using the following 4 existing validated scales: the Risk‐Taking Scale (RTS), Stress from Uncertainty Scale (SUS), the Fear of Malpractice Scale (FMS), and the Need for (Cognitive) Closure Scale (NCC). We used Cronbach's α to assess the reliability of each scale and performed multivariable linear regressions to analyze the association between the score for each scale and clinician characteristics. Results: Of 1458 ED clinicians recruited for participation, 1116 (76.5%) responded from 93% of acute care hospitals in Massachusetts. Each of the 4 scales demonstrated high internal consistency reliability with Cronbach's αs ranging from 0.76 to 0.92. The 4 scales also were moderately correlated with one another (0.08 to 0.54; all P < 0.05). The multivariable results demonstrated differences between physicians and APCs, with physicians showing a greater tolerance for risk or uncertainty (NCC difference, −3.58 [95% confidence interval, CI, −5.26 to −1.90]; SUS difference, −3.14 [95% CI: −4.99 to −1.29]) and a higher concern about malpractice (FMS difference, 1.14 [95% CI, 0.11–2.17]). Differences were also observed based on clinician age (a proxy for years of experience), with greater age associated with greater tolerance of risk or uncertainty (age older than 50 years compared with age 35 years and younger; NCC difference, −2.84 [95% CI, −4.69 to −1.00]; SUS difference, −4.71 [95% CI, −6, 74 to −2.68]) and less concern about malpractice (FMS difference, −3.19 [95% CI, −4.31 to −2.06]). There were no appreciable differences based on sex, and there were no consistent associations between scale scores and the practice and payment characteristics assessed. Conclusion: We found that risk attitudes of ED clinicians were associated with type of training (physician vs APC) and age (experience). These differences suggest one possible explanation for the observed differences in decision making.